Suture-based vs. pure plug-based vascular closure devices for VA-ECMO decannulation. (3rd October 2022) - Scherer, C; Theiss, H; Istrefi, M; Stocker, T J; Kupka, D; Luesebrink, E; Hausleiter, J; Hagl, C; Massberg, S; Orban, M
Abstract: Background: VA-ECMO is a valuable treatment option for patients in cardiogenic shock, but complications during decannulation may worsen the overall outcome. To date, no larger study has ever compared suture-based to pure plug-based vessel closure devices for VA-ECMO decannulation. Purpose: The aim of the study was to compare the efficacy and safety of suture-based to pure plug-based vascular closure devices for veno-arterial extracorporeal membrane oxygenation (VA-ECMO) decannulation for patients with cardiogenic shock. Methods: In this retrospective study, the outcome of 33 patients with suture-based closure devices implanted between 02/2019 to 05/2020 were compared to 38 patients with plug-based closured device implanted between 06/2020 to 11/2021. Results: Closure device success rate was 88% in the suture-based group versus 97% in the plug-based group (Figure 1, p=0.27). Median number of devices used was two for patients with suture-based closure device and 1 for patients with plug-based closure device (p<0.01). Severe bleeding was more frequent in the suture-based (21%) compared to the plug-based group (3%) (Figure 2, p=0.04). Ischemic complications occurred in 6% with suture-based and 5% with plug-based device (p=1.00). Pseudoaneurysm formation was detected in 3% in both groups (p=1.00). Application of the femoral compression system was required in 27% of patient with suture-based closure device and 11% of patients with plug-based closure device (p=0.13). No switch to open vascular surgery due to closure device failure occurred in both groups. Conclusions: Based on our retrospective analysis, we propose that plug-based vascular closure should be the preferred option for VA-ECMO decannulation. This hypothesis should be further tested in a randomized trial. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft